Techno-economics analysis of battery energy storage system (BESS) design for virtual power plant (VPP)-a case study in Malaysia - Wan Abdullah, Wan Syakirah; Osman, Miszaina; Ab Kadir, Mohd Zainal Abidin; Verayiah, Renuga; Ab Aziz, Nur Fadilah; Abdul Rasheed, Mohamed (Elsevier BV, 2021)
Renewable Energy (RE) penetration to power system has been a trend in recent years. Malaysia under the new RE target has a vision to achieve 20% of RE in energy mix by 2025. Flexibility and stability of power system can be a concern due to high penetration of RE in the system. Battery Energy Storage System (BESS) has been identified as one of the possible solutions to mitigate this issue. This paper will discuss the capabilities of this technology to reduce peak demand charge and potential to solve power system issues and the techno-economic analysis for this technology. This covers technical and economic analysis to ensure viability and feasibility of this technology. This is a novel analysis in terms of Malaysian energy market as BESS is considered relatively new technology and still in early stage in terms of commercial deployment.